A sustainable, ultratough, and ready‐to‐use adhesive heating patch driven by solar/electric dual energy. Issue 4 (28th December 2021) - Wang, Jiqiang; Sun, Shengtong; Wu, Peiyi
Abstract: Developing a versatile and durable photothermal coating is of great interest for the future large‐scale utilization of abundant solar energy. However, existing photothermal coatings that rely on the assembly of rigid solar absorbing nanomaterials have often limitations in both mechanical robustness and multienergy coupling for sustainable heating. Here, we report a ready‐to‐use and ultratough adhesive heating patch with the integrated abilities of photo‐/electrothermal conversion and damage self‐diagnosis. The patch is composed of interconnected carbon microfibers filtrated with photo‐curable self‐adhesive resin that can readily stick on the substrate, and postcuring rapidly toughens the patch resulting in high mechanical toughness (9.1 MJ/m 3 ), high electrical conductivity (5 S/cm), strong adhesion (0.7‐4.6 MPa), as well as high solar‐thermal conversion (∼ 85.3%) and Joule heating (81.6°C/W) efficiencies. To demonstrate its application, the adhered patch on oil pipelines can rapidly reduce the viscosity of heavy crude oil to ∼100 Pa s under the action of solar radiation or Joule heating, allowing for oil's easy flow in pipelines in all‐weather and, thus, alleviating the use of expensive fired heaters at heating stations. Abstract : A ready‐to‐use and ultratough adhesive heating patch with excellent environmental stability, multienergy coupling, and damage self‐monitoring ability is reported. The patch can be used like adhesive tapes, readily sticks on the various substrates, and rapidly cures by UV or solar light. Such a facilely produced patch simultaneously meets the requirements of high durability and versatility for large‐scale photothermal technologies that may be used outdoors for long‐distance pipeline transportation of crude oil.